STRATEGI GURU MATA PELAJARAN FIKIH DALAM MENINGKATKAN MOTIVASI SALAT WAJIB PADA SISWA KELAS VII DI MTS YASTI SEKABAU TAHUN PELAJARAN 2022-2023 - Desi; Nuraini; Asyura, Muhammad (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This thesis discusses the strategies of Fiqh subject teachers in increasing motivation for mandatory prayers in class VII students at MTs Yasti Sekabau. This research has two research objectives, including the following: 1) to find out the strategies of Jurisprudence teachers in implementing learning in increasing motivation for mandatory prayers in class VII students at MTs Yasti Sekabau for the 2022-2023 academic year. 2) find out the results of the implementation of the Jurisprudence subject teacher in fostering appreciation for the motivation for mandatory prayers in class VII students at MTs Yasti Sekabau for the 2022-2023 academic year. This research uses a qualitative approach while this type of research is phenomenological research. There are three data collection techniques in this research, namely observation, interviews and documentation. Meanwhile, the data analysis techniques used are data reduction, data display or data presentation, and drawing conclusions or verification. Then the data validity checking techniques used are triangulation and member check. The results of this research are: The strategy for the Jurisprudence subject teacher to carry out learning in increasing motivation for mandatory prayers in class VII students at MTs Yasti Sekabau is as follows: Select and use learning strategies that suit the students' characteristics and understanding. 1) Using learning steps. 2) Providing motivation to students, both intrinsic motivation and extrinsic motivation. The results of the Jurisprudence subject teacher fostering appreciation for the motivation for mandatory prayers in class VII students at MTs Yasti Sekabau, namely by 1) explaining or providing an understanding of the benefits or wisdom contained in prayer. 2) provide character education. 3) model interactions or approaches to students. 4) emphasize material related to prayer.